Cymbopogon citratus Essential Oil Protects Tubular Renal Cells against Ischemia/Reoxygenation Injury - Involvement Nrf2/Keap1 Pathway - Duaran Lopes de Sousa; Mary Anne Medeiros Bandeira; Igor Lima Soares; Bruna Ribeiro Duque; Mac Dionys Rodrigues da Costa; Glautemberg de Almeida Viana; Emanuel Paula Magalhães; Ramon Róseo Paula Pessoa Bezerra de Menezes; Tiago Lima Sampaio; Márcia Machado Marinho; Alice Maria Costa Martins (Brazilian Archives of Biology and Technology)
Abstract Ischemia and reoxygenation (I/R) cause acute kidney injury with progression related to oxidative damage, mitochondrial dysfunction and cell death. Nrf2-Keap1 pathway is involved in this process. Cymbopogon citratus, used in popular medicine, is a promising source of bioactive antioxidant compounds. This study investigated the cytoprotective effect of C. citratus essential oil (CCEO) in an I/R model, and the interaction of CCEO major components with the Nrf2-Keap1 pathway in silico. CCEO was characterized by GC-MS, presenting citral isomers trans-geranial (55.48%) and cis-neral (35.40%). I/R decreased LLC-MK2 kidney cells viability by around 50% (MTT assay); CCEO increased cell viability and decreased loss of membrane integrity (Flow cytometry with 7-AAD). CCEO decreased ROS and mitochondrial depolarization and reduced the release of KIM-1, a marker of tubular injury (ELISA). CCEO ameliorated ultrastructural (DCF and Rho123 staining) changes induced by I/R saw in scanning electron microscopy, such as volume retraction, formation of apoptotic bodies, and adhesion to extracellular matrix decrease. The interactions of citral isomers with Keap1 were made through molecular docking. Geranial and neral demonstrated a ∆G around -5.0 kcal/mol with Keap1, binding to some amino acids common to co-crystallized ligand. So, the cytoprotective effect in renal cells may be related to the interaction of citral (neral and geranial) with the Nrf2/Keap1 pathway.